KAJIAN STILISTIKA DALAM KITAB SUCI DHAMMAPADA : (Representasi Gaya Bahasa Pada Syair-Syair Puppha Vagga dan Naga Vagga) - Santi Paramita (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2020)
This book has a characteristic style of language that is different. Very rich in literary transfer, as well as his unique poetic expressions and additions to legendary stories when examined in the aspect of stylistics. This study aims to determine and describe the style of language and its functions used by the Buddha in the Dhammapada Scriptures, specifically Puppha Vagga and Naga Vaggha verses. This study uses a stylistic approach, which is an approach that departs from the assumption, that language has an important role and role in the presence of literary works. Data collection is done by observation-interpretation-note taking techniques, while the data analysis technique used is descriptive-qualitative technique. The results showed that the Buddha used the style of words and style of sentences and discourse. Word styles used include: figurative language and imagery. The figures of speech used include: simile, association, personification, and symbolic. Images that are used include visual images, feeling images, and olfactory images. The most dominant image of its use is the image of smell and feeling. The style of sentences and discourse used in the form of means of rhetoric include repetition and rhetorical questions. The dominant means of rhetoric are repetition and rhetorical questions. The implication of language style is in term of meaning